Staphylococcus aureus: A brief review - Maliha Gulzar; Asima Zehra (International Journal of Veterinary Science and Research - Peertechz Publications, 2018)
Staphylococcus aureus, also known as "golden staph", is a gram-positive coccus belonging to the class Bacilli, order Bacillales, family Staphylococcaceae and genus Staphylococcus [1]. It is a facultative anaerobe often positive for catalase and nitrate reduction and is coagulase variable i.e. maybe cogulase positive or negative [2]. The bacterium is non-motile, non-spore forming and appearing as bunch of grapes, microscopically. On blood agar it shows large, round, golden-yellow colonies often with hemolysis.